Issues of Developing the Tool for Diagnosis of Energy Efficiency Level of Russian Regions’ Economy - Kreydenko, Tatiana Fedorovna; Chernyaev, Maxim Vasilyevich; Grigorieva, Elena Mikhaylovna (International Journal of Energy Economics and Policy, 2018)
The article gives analysis of approaches to evaluation of energy efficiency of a territory’s economy established in the global and Russian practice; identifies key features of implementation of index approach to diagnostics based on common techniques of decomposition, or factor, analysis of indices; indicative approach based on calculation of energy security and energy performance figures. Comparison of multi-dimensional and ranking approaches in usage of energy efficiency evaluation diagnostics tools was also performed. Based on application of the existing tools the characteristics of present-day state of energy efficiency of Russian economy was given and key problems of increasing thereof were emphasized. The authors suggested mechanism of usage of the indicative method in diagnostics of energy efficiency level of a territory’s economy, which ensures identification of the weakest points of energy efficiency enhancement, forecasting of consequences thereof, taking of contemporary managerial solutions with regard to further actions. Keywords: regional economy; energy efficiency enhancement; sustainable social and economic development. JEL Classifications: O10, R10